The reality of application the administrative governance at King Abdulaziz University from point of view of teaching faculty members - Alzahrani, Mona Mohammed; Badawood, Omar Mohammed (Journal of Educational and Psychological Sciences, 2023)
The research aims to identify the reality of application the administrative governance represented in dimensions: (transparency, accountability and participation) at King Abdulaziz University from the point of view of teaching faculty members. The researcher applied the descriptive survey approach, and used the "questionnaire” as a tool to collect data, as it was applied to a random sample of (83) members of teaching faculty members of King Abdulaziz University, which represent (1.4%) of the original community, and the results of the research reached: The degree of application of administrative governance at King Abdulaziz University from the point of view of teaching faculty members came with a medium degree in all dimensions, and the research showed the existence of statistically significant differences in the degree of administrative governance application and in all dimensions are related to the gender variable in favor of females, and also the research showed that there are statistically significant differences in the degree of application of administrative governance in the two dimensions of accountability and participation, which are related to the degree variable in favor of a teaching faculty member in all dimensions except for the transparency dimension. The research concluded with several recommendations, establish an Administrative Governance Unit at King Abdulaziz University and with an objective to develop and audit the governance systems in the sectors of the university and following up on their implementation.